1994
DOI: 10.1111/j.1365-2788.1994.tb00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐infarct dementia in Down's syndrome

Abstract: ABSTRACT. In spite of a burgeoning literature on the association of Down's syndrome with Alzheimer's disease, the occurrence of multi‐infarct dementia has largely been overlooked. A 55‐year‐old woman with Down's syndrome in whom a dementing process was associated with evidence of significant cerebrovascular disease is reported here. It is considered that she sustained both multi‐infarct dementia and probable Alzheimer's disease. It is suggested that such cases are under‐reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Interestingly, there are no systematic studies in DS brain to evaluate the distribution of CAA with age, which could be accomplished by MR studies or by autopsy. With increased CAA and Aβ1-40 in DS, interestingly, VCID (or multi-infarct dementia as it was termed then) per se is rare with only one case report in the literature of a 55-year old woman with DS [19]. …”
Section: Cerebrovascular Pathology In Down Syndromementioning
confidence: 99%
“…Interestingly, there are no systematic studies in DS brain to evaluate the distribution of CAA with age, which could be accomplished by MR studies or by autopsy. With increased CAA and Aβ1-40 in DS, interestingly, VCID (or multi-infarct dementia as it was termed then) per se is rare with only one case report in the literature of a 55-year old woman with DS [19]. …”
Section: Cerebrovascular Pathology In Down Syndromementioning
confidence: 99%
“…Extensive cerebrovascular hemorrhages and stroke are associated with CAA in DS [ 8 , 18 , 31 , 39 , 40 , 43 ] in most studies but not in all [ 30 , 35 ]; the majority of these studies are based on small autopsy series or case reports. Despite increased CAA in DS with age, VCID (or multi-infarct dementia as it was termed then [ 16 ]) is rare with only one case report in the literature of a 55-year old woman with DS.…”
Section: Introductionmentioning
confidence: 99%
“…1996). Also, there are concerns that cerebro‐vascular disease and multi‐infarct dementia may be missed or under‐reported (Collacott et al. 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For example, people with learning disabilities may show premature ageing of their immune systems and they also have a higher risk of congenital heart disease (Evenhuis et al 2001) and there are some concerns too of the development of or the increase in seizure activity (McVicker et al 1994;Johannssen et al 1996). Also, there are concerns that cerebro-vascular disease and multiinfarct dementia may be missed or under-reported (Collacott et al 1994). • Other medical conditions such as thyroid problems may also result in behaviour that may look like the consequences of dementia (Janicki & Dalton 1999) and a paper by Nicholson et al (1994) reported that an ongoing longitudinal study was showing that six of nine adults with Down syndrome diagnosed with dementia had autoimmune thyroiditis.…”
Section: Introductionmentioning
confidence: 99%